Economic evaluation of Composite carp culture in Odisha - Shasani, Simantini; Kumar Das, Manoj; Kumar De, Himansu; Saha, Gour Sundar; Mahapatra, Abhijit Sinha (Fishery Technology, 2021)
The present study was conducted in Dhenkanal district of Odisha to analyze the cost and returns of composite carp culture. Data were collected from 71 fish farmers through personal interviews. Farmers had an average pond area of 0.4 ha and mean fish yield was found to be 2.1 t/ha/y. Rate of return on total investment (ROI) and Benefit-Cost ratio (B:C ratio) for adopters and non-adopters were worked out as 72.83%; 1.73 and 38.62%; 1.39 respectively. Feed constituted the maximum share (37%) in cost of production of fish followed by lease value of pond (15%). Lack of knowledge about scientific fish farming, high cost of supplementary feeding, lack of financial support and non-availability of bigger sized fingerlings were identified as the major constraints to adoption of composite carp culture technology. The economic appraisal clearly established carp culture as a profitable venture.